Plasma Fibronectin Enhances Fibrinolytic System In Vitro - Gilboa, Nisan; Kaplan, John E (Thrombosis and Haemostasis, 1985)
The effects of plasma fibronectin on the fibrinolytic system were studied in vitro. Fibronectin caused a time and concentration-dependent increase (up to 99% with 330 ug/ml) in the amidolytic activity of tissue plasminogen activator (TPA) but not of urokinase. In the presence of fibronectin the Km of the amidolytic activity of TPA decreased without a change in Vmax. It also caused a concentration-dependent increase in lys-plas-minogen activation by TPA (up to 825% with 375 ug/ml) and by urokinase (up to 400% with 250 ug/ml), as well as in the amidolytic activity of plasmin (up to 55% with 300 ug/ml). Fibronectin did not enhance the activation of glu-plasminogen. In the presence of fibronectin the Km of lys-plasminogen activation decreased without a change in Vmax. In purified systems fibronectin significantly shortened the clot lysis time (CLT) by up to 28% and 30% in TPA- and plasmin-activated lysis, respectively. The presence of Ca2+ did not change fibronectin’s effect on CLT. Clots of non-fibronectin-depleted plasma were lysed up to about twice as fast as the clots of fibronectin-depleted plasma. In conclusion, physiologic concentrations of fibronectin enhanced the fibrinolytic system in vitro. Further studies will be required to elucidate the mechanisms involved and to document whether fibronectin has a similar effect in vivo.
Keywords: Fibronectin; Tissue plasminogen activator; Urokinase; Plasmin; Plasminogen; Fibrinolysis